Analysis of the Results of Sonographic Screening Examinations According to the Maternity Guidelines Before and After the Introduction of the Extended Basic Screening (IIb Screening) in Hesse - Schmand, Christine; Misselwitz, Björn; Hudel, Helge; Bedei, Ivonne; Wolter, Aline; Schenk, Johanna; Keil, Corinna; Köhler, Siegmund; Axt-Fliedner, Roland (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Aim of the Study The aim of the study is to examine the detection rates of malformations before and after the introduction of extended basic screening in Hesse by the Federal Joint Committee (Gemeinsamer Bundesausschuss, GQH) on July 1, 2013.Method This is a retrospective, mainly exploratory data analysis of quality assurance data from the Office for Quality Assurance in Hesse (GQH). The data was collected in the period from January 1, 2010 to December 31, 2016 in the obstetric departments of the Hessian hospitals using documentation forms. The classification and evaluation of the diagnoses is based on ICD-10-GM-2019.Results At least one malformation is present in 0.7% of the cases. With a share of 30.0%, most of the congenital malformations are from the musculoskeletal system. 12.2% of the malformations come from the facial cleft, closely followed by malformations of the circulatory system with 11.3%. The highest prenatal detection rate (PDR) is found in congenital malformations of the nervous system at 56.8%. The lowest PDR is found in those of the genital organs with 2.1%. The PDR of cardiovascular malformations is 32.9%. Overall, a PDR of 25.2% is achieved. There was no change in the number of prenatal malformation diagnoses after the introduction of extended basic ultrasound. The distribution of malformation diagnoses not detected prenatally to the organ systems also has not changed after the introduction.Conclusion The introduction of extended basic ultrasound did not bring the desired improvement with regard to the PDR in Hesse. Alternative approaches should be considered.
Keywords: Obstetrics; Gynecology; Education, Training, Quality Assurance